2009
DOI: 10.1063/1.3082936
|View full text |Cite
|
Sign up to set email alerts
|

Observation of ion cyclotron range of frequencies mode conversion plasma flow drive on Alcator C-Mod

Abstract: Abstract. At modest3 He levels (n 3He /n e ~ 8-12%), in relatively low density D( 3 He) plasmas, e n ≤

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 45 publications
4
54
0
Order By: Relevance
“…324 Simulations with the TORIC code showed that the mechanism is through IC wave interaction with He 3 ions, while the shorter wavelength IBW only caused electron heating. 325 316 conversion regime. Although the stored energy increase is somewhat larger for the minority heating case, the toroidal rotation is much greater for mode conversion.…”
Section: B Icrf Flow Drivementioning
confidence: 99%
“…324 Simulations with the TORIC code showed that the mechanism is through IC wave interaction with He 3 ions, while the shorter wavelength IBW only caused electron heating. 325 316 conversion regime. Although the stored energy increase is somewhat larger for the minority heating case, the toroidal rotation is much greater for mode conversion.…”
Section: B Icrf Flow Drivementioning
confidence: 99%
“…This is especially important for extrapolations to next generation devices, in which the effectiveness of NBI is expected to be diminished. As such, these devices will depend more heavily on alternate heating schemes such as ion and electron wave heating and current drive, both of which have been observed experimentally to impact the plasma rotation [23,24,25,26,27,28,29]. In particular, the influence of electron heating on plasma rotation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16]). Although no consistent theoretical framework yet exists that solidly links the experimental evidence of flow driven on the one hand and the fate of the energy carried by the up-down asymmetric mode converted waves on the other hand, many believe that one of the main roles externally launched ICRF waves may play in future machines is to ensure flow drive which impacts on plasma confinement and stability.…”
Section: Introductionmentioning
confidence: 99%